Ta'ṡīr al-Wasīlah at-Taʿlīmiyyah at-Tafāʿuliyyah fī Tarqiyah Mafhūm at-Tarākīb an-Naḥwiyyah - Ulfa Fauziah Yarda; Hayati Hayati; Fajriyani Arsya (Rumah Jurnal IAIN Bukittinggi, 2022)
The problems in this research are that the students lack enthusiasm in learning grammatical structures, and the teacher did not use excellent and engaging learning media. So the students got bored and did not understand grammatical structures except a little, and most of them still felt that grammatical structures were the most challenging lesson. The research aims to show the use of interactive learning media in upgrading the concept of grammatical structures for the eighth-grade students at the Governmental Islamic Middle School 6 Agam. The writer used experiment research to consider the effect of interactive learning media on understanding grammatical structures. The population in this research is all eighth-grade students in the Governmental Islamic Middle School 6 Agam. The eighth grade consists of seven classes, and the writer takes the sample by Purposive Sampling. The research tools are observation, interview, and test. The research analysis used the t-test rule. The mean score for the post-test in the experimental class is 67,12. The mean score for the post-test in the control class is 60,44. The writer found that the result of the t count (2,049) and the t table (1,670), so the impact of the t count is more significant than the result of the t table. The difference between them means 0.379. The writer takes the conclusion that there is an effect of the interactive learning media in upgrading the concept of grammatical structures for the eighth-grade students at the Governmental Islamic Middle School 6 Agam.المشكلات في هذا البحث أنه قلة الحماس لدى الطلاب في تعلم التراكيب النحوية، ولم تستخدم المعلّمة الوسائل التعليمية الجيدة والممتعة، حتى يمل الطلاب ولم يفهموا التراكيب النحوية إلا قليلا ومعظمهم لا يزالون ويشعرون أن التراكيب النحوية أصعب الدرس. أما أغراض البحث هي لبيان استعمال الوسيلة التعليمية التفاعلية في ترقية مفهوم التراكيب النحوية لطلاب الفصل الثامن بالمدرسة المتوسطة الإسلامية الحكومية 6 آغام. استعملت الكاتبة البحث التجريبي لتنظر تأثير الوسيلة التعليمية التفاعلية على فهم التراكيب النحوية. والمجتمع في هذا البحث هو كل طلاب الفصل الثامن في المدرسة المتوسطة الإسلامية الحكومية 6 آغام. والفصل الثامن يتركب إلى سبعة فصول، وتأخذ الكاتبة العينة بطريقة Purposive Sampling. أما أدوات البحث هي الملاحظة والمقابلة والاختبار. واستعمال تحليل البحث قاعدة اختبار